Evaluation of Accounting Information Systems in Company Financial Management - Inez Adelia Lapian; Melani Pitria; Muhammad Maulida Haikal Nawawi; Sri Andini Cahyant; Galih Supraja (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to evaluate the impact of Accounting Information Systems (AIS) on the quality of financial reports through a literature review of ten relevant articles. The results of the analysis show that eight out of ten articles state that the implementation of AIS has a positive and significant impact on improving the quality of financial reports. The implementation of AIS is considered capable of improving the accuracy, relevance, and readability of financial reports and reducing errors caused by human error. The advantage of AIS lies in the computerized data processing process, which produces reports that are more reliable, relevant, and in accordance with applicable accounting standards. However, two other articles, namely the work of Riska Ramadani et al. (2022) and Nishrina Atharrizka et al. (2021), revealed that AIS did not have a significant impact on the quality of financial reports. In this case, other factors such as human resource capabilities and the effectiveness of internal control are more dominant elements in determining the quality of financial reports. This finding shows that the effectiveness of AIS in improving the quality of financial reports is highly dependent on other supporting factors, such as increasing human resource capacity and strengthening the internal control system. Therefore, maximum implementation of SIA, supported by adequate management of supporting factors, is the key to producing high-quality and reliable financial reports for strategic decision making.